Nuwe Testament-geskrifte as kanon: Die vraag na " n uitgebreide databasis vir historiese-Jesus ondersoek - Geyser, P. A. (Hervormde teologiese studies, 1999)
New Testament witings as canon: The quest for an extended database for historical Jesus research. The aim of this article is to re-establish the disparate traditions concerning the origins and growth of documents that developed into the New Testament canon. The article reflects the insights of Lee McDonald's book The formation of the Christian Biblical canon. Some of the accepted notions concerning the canon come under scrutiny, for instance that the New Tesament canon was completed before the end of the second century. The aricle concludes with the question whether the New Testament canon should be revised in the light of recent histoical Jesus studies. History and tradition plead against an incisive revision. The only option seems to be a scholar's edition of a revised list for ecclesiastical use.